(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
The business centre also rapidly becoming an e-commerce centre. Everything can be bought on the web from needle to ship. Old and new entrants are already in the process about thinking of innovative structures to sell their products and services to the existing players and contestants. Electronic Industry is nothing than a different way of supporting or improving traditional enterprises. Or maybe e-commerce has brought innovative market shifts. This is a problem-solving innovation that dramatically changes the traditional business system. Ecommerce paves the way for our nation’s enormous business growth. The growth of the web customers expanded further. Ecommerce has led to the growth of the online travel industry through various approaches and included an additional corporate sector by our online shopping industry. The current study aims at historical development of e-commerce, e-commerce advantages, e-commerce opportunities, reasons for e-commerce growth, In India, e-commerce Are, Key Drivers In India, E-commerce growth and prospects E-commerce challenges, e-commerce issues.